Contrast‐enhanced ultrasound enables precision diagnosis of preoperative muscle invasion in bladder cancer: a prospective study - Qiyun Ou; Weibin Xie; Yunfang Yu; Bing Ou; Man Luo; Yongjian Chen; Weiwei Pan; Yiming Lai; Zhuohang Li; Jianqiu Kong; Zhuo Wu; Jingliang Ruan; et al. (MedComm)
Abstract Bladder cancer's high mortality underscores the need for precise staging, especially to differentiate between nonmuscle invasive bladder cancer (NMIBC) and muscle invasive bladder cancer (MIBC) types. This prospective study evaluated the efficacy of contrast‐enhanced ultrasound (CEUS) for preoperative staging, focusing on its ability to distinguish NMIBC from MIBC. Conducted from April 2020 to September 2021, the study involved 163 patients (median age: 64.0 years; 137 males, 26 females), with 133 NMIBC (81.6%) and 30 MIBC (18.4%). Each patient underwent CEUS followed by transurethral resection of bladder tumor or radical cystectomy. CEUS demonstrated high diagnostic accuracy in determining muscle invasion status (sensitivity 83.3%, specificity 92.5%, accuracy 90.8%, area under the receiver operating characteristic curve [AUC] 0.88). Comparative analyses against MRI (AUC 0.77) showed CEUS outperforming in muscle invasion detection. Combining CEUS with MRI improved diagnostic accuracy, particularly when MRI vesical imaging reporting and data system score was 3 points. The combined approach achieved an AUC of 0.73, with sensitivity, specificity, and accuracy of 76.2, 70.2, and 71.6%, respectively. Thus, CEUS emerges as a valuable diagnostic tool for preoperative staging of bladder cancer, particularly in its role in assessing muscle invasion status and thereby aiding in clinical decision‐making and intervention outcomes.